Inhibitory property of metabolite combinations produced from Lactobacillus plantarum strains - Choe, Di Wei; Foo, Hooi Ling; Loh, Teck Chwen; Bejo, Mohd Hair; Sazili, Awis Qurni (Universiti Putra Malaysia Press, 2013)
The inhibitory property of metabolite combinations produced from six different strains of Lactobacillus plantarum were evaluated in this study. The final pH of culture media and cell population of each strain were determined and the antimicrobial activity of the metabolite from individual strains and combinations were conducted against Pediococcus acidilactici as indicator microorganism. The lowest pH was observed in the media which were cultured with L. plantarum RG11 and RG14 (P < 0.05), while the highest cell population was found in L. plantarum RI11 and RG11. There was no significant difference in the inhibitory activity among the six individual strains. However, when the three strains of L. plantarum were combined, the combination of strains (TL1-RI11-RG11, strains RS5-RI11-RG11 and strains RI11-RG14-RG11) showed a higher level of inhibition. The metabolite combinations from L. plantarum strains could be potential pathogen inhibition compound in the food and feed industry.